Inflow turbulence generation methods with large eddy simulation for wind effects on tall buildings. (15th August 2015) - Yan, B.W.; Li, Q.S.
Highlights: Evaluate the performances of four inflow turbulence generation methods. Identify their advantages and limitations for LES of wind effects on tall building. Provide remedial measures to improve the performances of the methods. Propose a procedure for accurate LES of wind effects on tall building. Abstract: Generation of turbulent inflow conditions matching realistic wind flow characteristics in atmospheric boundary layer (ABL) is essential for accurate predictions of wind effects on buildings and structures using large eddy simulation (LES). It is thus necessary to evaluate the performances of different inflow turbulence generation techniques. In this study, four inflow turbulence generation methods (including three synthetic turbulence methods and the recycling method) were used to simulate wind flows in ABL for LES of wind loadings on a tall building. The advantages and limitations of these inflow turbulence generation methods were discussed through comparisons with available wind tunnel measurements and previous numerical simulation results. Several remedial measures were presented to improve the performances of these inflow turbulence generation methods. The findings of this paper are of use and interest to researchers and designers involved in the wind-resistant design of tall buildings, since one can follow the established procedure to predict the dynamic wind loadings on tall buildings by LES.